Become an accelerator leader : accelerate yourself, others, and your organization to maximize impact - Rohrs, Alvin (Columbus, Ohio : Gatekeeper Press, 2019)
Fighter pilots experience the fastest acceleration on earth. However, during training, the expression, (3z(Bthat pilot is all thrust and no vector,(3y (Bcan be heard. It describes a pilot who is going nowhere fast. That concept holds true in our lives and especially in business. We live in an age of instant information, where everything moves at the speed of light. Do you ever feel that you are going fast but getting nowhere? Accelerator Leaders learn how to focus and act so that their acceleration results in real impact. Discover how to be an Accelerator Leader to accelerate yourself, those around you and your organization.s
oif 17/06/2021
Loans
Keywords: Leadership; Organizational behaviour